Research progress of glutathione peroxidase family (GPX) in redoxidation - Jun Pei; Jun Pei; Xingyu Pan; Guanghui Wei; Guanghui Wei; Yi Hua; Yi Hua (Frontiers Media S.A., 2023)
Maintaining the balance of a cell's redox function is key to determining cell fate. In the critical redox system of mammalian cells, glutathione peroxidase (GPX) is the most prominent family of proteins with a multifaceted function that affects almost all cellular processes. A total of eight members of the GPX family are currently found, namely GPX1-GPX8. They have long been used as antioxidant enzymes to play an important role in combating oxidative stress and maintaining redox balance. However, each member of the GPX family has a different mechanism of action and site of action in maintaining redox balance. GPX1-4 and GPX6 use selenocysteine as the active center to catalyze the reduction of H2O2 or organic hydroperoxides to water or corresponding alcohols, thereby reducing their toxicity and maintaining redox balance. In addition to reducing H2O2 and small molecule hydroperoxides, GPX4 is also capable of reducing complex lipid compounds. It is the only enzyme in the GPX family that directly reduces and destroys lipid hydroperoxides. The active sites of GPX5 and GPX7-GPX8 do not contain selenium cysteine (Secys), but instead, have cysteine residues (Cys) as their active sites. GPX5 is mainly expressed in epididymal tissue and plays a role in protecting sperm from oxidative stress. Both enzymes, GPX7 and GPX8, are located in the endoplasmic reticulum and are necessary enzymes involved in the oxidative folding of endoplasmic reticulum proteins, and GPX8 also plays an important role in the regulation of Ca2+ in the endoplasmic reticulum. With an in-depth understanding of the role of the GPX family members in health and disease development, redox balance has become the functional core of GPX family, in order to further clarify the expression and regulatory mechanism of each member in the redox process, we reviewed GPX family members separately.